Mathematics teaching strategies and 4th-grade student achievement in Arab countries: evidence from TIMSS 2019 data - AlSalouli, Misfer; AlGhamdi, Mohammed; AlShamrani, Saeed; AlMufti, Abdu; Aldarwani, Bakeel; Jakubowski, Maciej (Humanities & social sciences communications, 2024)
This paper analyses the most effective teaching strategies in 4th-grade mathematics students, considering estimations for Arab countries participating in the TIMSS 2019 assessment. The paper aims to enable educators to design curricula and implement teaching strategies that align with the specific characteristics of these countries. It contributes to the literature by a detailed analysis of the most effective teaching strategies for students in Arab countries and by developing a methodology for assessing variability in mathematics performance. The method employs multilevel models, which allow us to assess where most of the variability in mathematics achievements is found, comparing the attainment between and within classrooms. The results found that nearly half of the variance was associated with differences in classroom achievement. The results show that mathematics strategies involving teacher-guided instruction are negatively associated with achievements. The opposite is observed for strategies involving independent study. The paper also shows that relying on these strategies does not alter the relationship between socioeconomic background and achievement. In addition, the results show the importance of positive student attitudes towards mathematics and of promoting a culture where students value and enjoy learning the subject. This can be achieved through engaging instructional practices and creating student collaboration and exploration opportunities.